PENGARUH KUALITAS PRODUK DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA PT. DUTA AYUMAS PERSADA NAMORAMBE DELI SERDANG - Kristi Endah Ndilosa Ginting; Agnes Maria Simarmata; Yenny Silalahi; Putra Gulo (Sekolah Tinggi Ilmu Ekonomi-LMII Medan, 2019)
The purpose of the study was to examine and analyze the influence of the product quality and promotion on purchasing decisions at PT. Duta Ayumas Persada Namorambe Deli Serdang. The population in this study were customers who make purchases at at PT. Duta Ayumas Persada Namorambe Deli Serdang, and were taken 265 customers as a sample. Before the regression model obtained was used to test the hypothesis, the model was tested in the classical assumption. The classic assumption test used includes: normality test, multicollinearity test, and heteroscedesticity test. This data analysis model used multiple regression analysis. The results of the study were product quality and promotion partially and simultaneously have a significant effect on purchasing decisions PT. Duta Ayumas Persada Namorambe Deli Serdang.